Minitags for small molecules: detecting targets of reactive small molecules in living plant tissues using 'click chemistry'. - Kaschani, F; Verhelst, S; van Swieten, P; Verdoes, M; Wong, C; Wang, Z; Kaiser, M; Overkleeft, H; Bogyo, M; van der Hoorn, R (2009)
Small molecules offer unprecedented opportunities for plant research since plants respond to, metabolize, and react with a diverse range of endogenous and exogenous small molecules. Many of these small molecules become covalently attached to proteins. To display these small molecule targets in plants, we introduce a two-step labelling method for minitagged small molecules. Minitags are small chemical moieties (azide or alkyne) that are inert under biological conditions and have little influence on the membrane permeability and specificity of the small molecule. After labelling, proteomes are extracted under denaturing conditions and minitagged proteins are coupled to reporter tags through a 'click chemistry' reaction. We introduce this two-step labelling procedure in plants by studying the well-characterized targets of E-64, a small molecule cysteine protease inhibitor. In contrast to biotinylated E-64, minitagged E-64 efficiently labels vacuolar proteases in vivo. We displayed, purified and identified targets of a minitagged inhibitor that targets the proteasome and cysteine proteases in living plant cells. Chemical interference assays with inhibitors showed that MG132, a frequently used proteasome inhibitor, preferentially inhibits cysteine proteases in vivo. The two-step labelling procedure can be applied on detached leaves, cell cultures, seedlings and other living plant tissues and, when combined with photoreactive groups, can be used to identify targets of herbicides, phytohormones and reactive small molecules selected from chemical genetic screens.